Integrasi Nilai Moderasi Beragama dalam Kurikulum Nasional: Studi Telaah terhadap Pendidikan Umum dan Keagamaan di Indonesia - Aguslani, Aguslani (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
This article aims to analyze the integration of religious moderation values within Indonesia’s national education curriculum, both in general education institutions under the Ministry of Education and Culture and in religious institutions under the Ministry of Religious Affairs. This study is motivated by the need to strengthen moderate religious character in response to the rising threat of radicalism and intolerance in educational environments. Employing a qualitative method through a descriptive-analytical approach of curriculum policy documents and institutional practices, this article finds that the Merdeka Curriculum and its projects—Pancasila Student Profile (P5) and the Rahmatan lil ‘Alamin Student Profile (PPRA)—have incorporated religious moderation values. These include tolerance, civility, balance, and openness to diversity. The findings show that although the curriculum accommodates these values, challenges remain in its implementation, particularly regarding teacher competence, teaching resources, and the influence of digital information. Therefore, the article recommends strengthening teacher training, regulating digital religious content, and fostering synergy between government, schools, and communities to embed inclusive and moderate religious values in the curriculum. Keywords: Religious Moderation; National Curriculum; Character Education; Pancasila Student Profile; Islamic Education